Tissue Doppler Right Ventricle Myocardial Performance Index (TDI RV-MPI) Versus Tricuspid Annular Plane Systolic Excursion (TAPSE) in Evaluation of RV dysfunction in Patients with or without LV dysfunction - Tamanna, Rownak Jahan; Rahman, Aparna; Hoque, Shabnam Jahan (Bangladesh Critical Care Journal, 2024)
Introduction: Cardiovascular disease remains a leading cause of death. Right ventricular (RV) function is a strong predictor of outcome in many cardiovascular diseases, but its significance is often neglected. It has often been coined “the forgotten chamber. RV dysfunction may be secondary to left ventricle (LV) dysfunction as a consequence of “Ventricular Interdependence”. As RV dysfunction is associated with high in-hospital morbidity and mortality, early reorganization of RV dysfunction is warranted; but until today it remains a challenging task because of complex structure and asymmetric shape of RV. Objective: Our objective was to compare the efficacy of Tissue Doppler Right Ventricle Myocardial Performance Index (TDI RV-MPI) with Tricuspid Annular Plane Systolic Excursion (TAPSE), as a predictor of RV Systolic dysfunction. Methods: This was a cross-sectional study in patients undergoing comprehensive Transthoracic Echocardiography for any indication. Our aim was to compare Tissue Doppler Right ventricle Myocardial Performance Index (TDI RV-MPI) with TAPSE to predict RV function in patients with or without LV dysfunction .The current study recruited 100 patients who presented to the Cardiology Clinic of Lab Aid Cardiac Hospital. In addition to calculation of conventional, quantitative LVEF done in 2D guided M-mode in Para-sternal long-axis view, RV function was assessed in all subjects by measurement of Tricuspid Annular Plane Systolic Excursion (TAPSE) & Tissue Doppler RV Myocardial Performance Index (TDI RV-MPI). Both were compared in prediction of RV dysfunction in patients with or without LV systolic dysfunction Results: RV dysfunction was found in subjects with LV dysfunction by both TAPSE & TDI RV -MPI. RV dysfunction increased with reducing left ventricular ejection fraction. Normal TAPSE (~24 mm) was evidence of normal TDI RV-MPI (0.2594±0.03269, P<.001), consistent with normal RV function. Of note, reduced TAPSE (~12 mm) was at the same time was evidence of increased TDI RV-MPI (0.7550±0.06351, P<.001), suggestive of RV dysfunction. Simultaneously normal LVEF (~ 55%) was evidence of normal TAPSE (22±1.582 mm, P<.001) & normal TDI RV-MPI (0.25±.0509, P<.001). Reduced LVEF (~25%) was at the same time, evidence of reduced TAPSE (15.50±3.317 mm, P<.001) & increased TDI RV-MPI (0.66±.1150, P<.001). A statistically significant negative correlation of TDI RV-MPI (r=-0.927) was observed with TAPSE (p<0.001). Also statistically significant negative correlation of TDI RV-MPI (r=-0.798) and significant positive correlation of TAPSE (r=0.813) were observed with LVEF (p<0.001). In the analysis TDI RV-MPI maintained significant correlation with both LVEF & TAPSE. In linear regression analysis TAPSE & LVEF were significant independent predictor of TDI RV-MPI. Most important determinants of TDI RV-MPI was TAPSE (R=0.927, p<0.001) . Conclusion: This study demonstrated that in patients with LV dysfunction there was RV dysfunction due to ‘ventricular interdependence’ as detected by both TAPSE & TDI RV-MPI. TDI RV-MPI is a simple, sensitive, reproducible, noninvasive, non-geometirc echocadiographic parameter to provide global assessment of systolic and diastolic function of RV. It has the ability to detect RV dysfunction at an early stage, so as to reduce morbidity and mortality in these patients. It is evident that TDI RV-MPI can be a surrogate of TAPSE even with superior efficacy in RV functional assessment maintaining close relation with LVEF. These observations could guide decision making in daily clinical practice. Bangladesh Crit Care J September 2024; 12 (2): 105-112